Elimination of the world crisis (Article of B.D. Brutskus) - Boris D. Brutskus; Alexander M. Nikulin; Vladislav Afanasenkov (Крестьяноведение, 2025)
Boris Davidovich Brutskus (1874–1938) was a remarkable economist whose agrarian studies are usually attributed to A. V. Chayanov’s organization-production school. However, agrarian issues were only one aspect of Brutskus’s multifaceted intellectual heritage as a major specialist in Jewish migration and colonization in the late 19th — early 20th centuries, in the political-economic criticism of the Russian Revolution, Soviet economic system and socialism in general. He was an insightful expert not only in issues of the Russian and Soviet economic policy but also in international economic-political relations. In his theoretical and ideological views Brutskus was a consistent supporter of liberalism but not an orthodox supporter of the homo economicus model. He spoke with deep respect and understanding about worldview values of socialism of both populist and Marxist directions, which were associated with the ideas of cooperative family economies and a socially oriented state, and emphasized that the market, free enterprise and economic freedom were fundamental conditions for any freedom in principle. With the Bolsheviks coming to power, during the civil war, Brutskus consistently and convincingly criticized the Soviet economic policy, for which the United State Political Administration (OGPU) expelled him on the so-called philosophical steamship to Germany. In Europe, until the early 1930s, Brutskus lectured on agrarian issues and political economy at the Russian Scientific Institute in Berlin and taught at the Yiddish University in Vilnius. After the Nazis came to power, he moved to Paris, and in 1935 emigrated to Palestine, where he headed the Department of Agricultural Economics and Policy at the University of Jerusalem, which was established with funds from the Jewish National Fund and at which he conducted research and taught until his death in 1938. Brutskus “was very enthusiastic about not only teaching but also practical activities to promote Jewish agriculture”. Brutskus’s great contribution to the developing Jewish agricultural and economic science was recognized and highly praised: his course of lectures was published posthumously, and the national journalism called him a Jewish genius of our time. Brutskus was an incredibly gifted and prolific economist and publicist, his analytical articles on the most current social-economic events of the 1920s and 1930s were published in newspapers and magazines not only in the Russian émigré press but also in national languages in periodicals of some European and North American countries. Thereby, it is not surprising that the article “Elimination of the world crisis”, which was discovered in B.D. Brutskus’s collection in the Central Archive for History of the Jewish People and which the author had prepared for publication but had not managed to publish, provides an overview of fundamental contradictions and probable alternatives for political-economic development of the world economy recovering with difficulty and in contradictory ways from the Great Depression in the second half of the 1930s. In this article, Brutskus identifies those groups of countries and key sectors of the economy that overcame consequences of the world crisis in different ways. This multipolarity of political-economic development caused Brutskus concern mainly due to the strengthening tendencies of bureaucratic autarkization of economies in some countries preparing for war. At the end of the article, Brutskus prophetically warns that the implementation of the German slogan “guns instead of butter” under declining international movement of migrants, capital, goods and increasing political-economic polarization of countries leads to an escalation of international tension and future military-political conflicts.